Review on non-isolated DC-DC converters and their control techniques for renewable energy applications - Farhan Mumtaz (Elsevier, 2021)
In recent times, the need for energy consumption is drastically increasing to fulfill the global requirements of commercial and domestic consumer demands. Energy generation using conventional methods such as oil and gas are not appreciated in the modern era since they are the major contributors for pollution and global warming. To tackle these issues, energy generation using hybrid renewable energy is being opted and studied universally. However, renewable energy sources have their fair share of drawbacks such as photovoltaic systems rely on the surrounding irradiance and temperature, wind system experiences irregular wind speed, and fuel cells are expensive and less efficient. Also, the energy extracted from renewable sources persist with stochastic behavior. To deal with these issues, researchers utilize different power electronic devices such as inverters, active power filters, voltage regulators, power quality conditioners, and DC-DC converters. Among these power electronic devices DC-DC converters are highly effective for DC voltage regulation and to improve the efficiency of renewable energy systems. Appropriate selection of the DC-DC converter is an important factor that has significant contribution in overall performance of the power systems. Besides, the selection of an efficient DC-DC converter topology, for its optimum operation integration of a suitable control technique is equally important. This paper highlights the characteristics of available and on-going trends of non-isolated converters that includes buck-boost, single ended primary inductor converter, cuk, z-source, zeta, and hybrid DC-DC converters based on the performance parameters that are analyzed using MATLAB Simulink. Control techniques that include proportional integral derivative (PID), slide mode control (SMC), model predictive control (MPC), state space modeling (SSM), and fuzzy logic control (FLC) are also discussed considering the parameters settling issue, response time and complexity while integrating with non-isolated DC-DC converters in power systems.